Numerical Study on the Movement Laws of Overlying Strata in Shallow-Buried Stope Based on the Goaf Compaction Effect - Guangchao Zhang; Guangzhe Tao; Miao Chen; You Li; Pan Li; Yonghui Lai (Shock and Vibration)
This study presents an integrated approach including the theoretical analysis and numerical modelling to investigate the failure characteristics of the overlying strata in the shallow-buried stope. The mechanical characteristics of the caving zone are first revealed and then calibrated by using the double-yield model. The theoretical results show that the mechanical properties of the collapsed rock mass are closely related to its crushing expansion coefficient and uniaxial compressive strength. The vertical stress of the collapsed rock mass increases slowly with the strain and then increases exponentially after a certain critical strain. The simulation indicates that the fracture zone volume is 1.7-1.8 times that of the caving zone in the 31108 working face, and the failure volume of the overlying strata is 9-10 times that of the stope. The simulated height of the caving zone and fracture zone is 9 m and 20 m, respectively. The comparison between the numerical and field measurement results demonstrates that the new evaluation method using shear-tensile strain behaviors can accurately predicate the height of the two zones. The proposed numerical method could be a viable alternative approach to two zones height calculation.